(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The aim of the study is to analyse the Economic profile of women workers, the factor affecting the quality of work life of Women workers in textile stores and to analyse the measure adopted by textile stores to improve the quality of work life of Women workers. The study uses both primary and secondary data. The area of study was Nagercoil and Marthandam, its limited to Kanniyakumari district. Data of 220 sample Women workers was collected for the study. The method of Sampling is Simple Random sampling technique. Statistical tools such as Factor analysis, Friedman Ranking techniques and Percentage analysis was used for the interpretation of results.